Effect of Anatomic Segment Involvement on Stereotactic Radiosurgery for Facial Nerve Schwannomas: An International Multicenter Cohort Study. (18th November 2021) - Mehta, Gautam U; Lekovic, Gregory P; Slattery, William H; Brackmann, Derald E; Long, Hao; Kano, Hideyuki; Kondziolka, Douglas; Mureb, Monica; Bernstein, Kenneth; Langlois, Anne-Marie; Mathieu, David; Nabeel, Ahmed M; et al.
Graphical Abstract: